2020
DOI: 10.1063/5.0013428
|View full text |Cite
|
Sign up to set email alerts
|

Metallic nanoparticle production and exposure/deposition system for toxicological research applications using zebrafish

Abstract: Metallic nanoparticles (NPs) have been accepted for various applications ranging from cosmetics to medicine. However, no method has been established in the scientific community that is capable of analyzing various metals, sizes, and levels of exposures without the concern of background chemical contaminations. We present here a system utilizing soft-landing ion mobility (SLIM) exposures of laser ablated metallic clusters capable of operating pressures of reduced vacuum (1 Torr) up to ambient (760 Torr) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The 6‐week‐old rats were then divided into two groups: Control and experimental (six rats in each group). The silver nanoparticles were generated as described in previous reports 35–38 . Using a laser ablation technique in the soft‐landing ion mobility (SLIM) instrument, under ambient atmospheric conditions, the rats were exposed to a cumulative concentration of 200 ppb AgNP ranging in diameter size from 1 to 100 nm, over a period 5 d, 4 h/days in a whole‐body‐type exposure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6‐week‐old rats were then divided into two groups: Control and experimental (six rats in each group). The silver nanoparticles were generated as described in previous reports 35–38 . Using a laser ablation technique in the soft‐landing ion mobility (SLIM) instrument, under ambient atmospheric conditions, the rats were exposed to a cumulative concentration of 200 ppb AgNP ranging in diameter size from 1 to 100 nm, over a period 5 d, 4 h/days in a whole‐body‐type exposure.…”
Section: Methodsmentioning
confidence: 99%
“…A previously published study using the SLIM instrument generated AgNP from our lab had characterized the AgNP concentration accumulating in the zebrafish liver tissue after a subacute exposure 38 using ICP‐MS. This study demonstrated that the AgNPs generated by the SLIM instrument vary in size from 1 to 100 nm and can be used for toxicity studies involving other animal models.…”
Section: Methodsmentioning
confidence: 99%